Patient-informed exploration of the aftermath of a diagnostic problem or mistake based on results of a national survey - Gleason, Kelly T.; Yuan, Christina T.; Haskell, Helen; Anderson, Michelle A.; Evered, Jane A.; McDonald, Kathryn M. (Frontiers in Health Services, 2024)
IntroductionDespite the prevalence and devastating consequences of diagnostic breakdowns, there have been minimal efforts to systematically collect patient insight into diagnostic problems and mistakes. Collaborating with patient advocates to guide how patient-derived insights are interpreted and used is a critical, yet often overlooked, approach to identifying actionable solutions that speak to patients' priorities.ObjectiveWe collaborated with patient advocate co-authors to guide our understanding of findings from a mixed methods survey on diagnostic problems and mistakes, and report implications for patient engagement at three levels of action: (1) individual level before, during, after encounters (micro); (2) within health service delivery systems (meso); and (3) policy advocacy (macro).MethodsOur research team applied narrative elicitation methods to conduct a novel survey about Americans' diagnostic experiences in a national, population-based survey. We shared early results with patient co-authors who highlighted the importance of further exploring how health systems and clinicians address the aftermath of diagnostic mishaps. Based on their input, we summarized the quantitative and qualitative survey results about the aftermath and worked with our patient co-authors to explore how findings might inform actionable next steps, including efforts to catalyze patient action, quality improvement efforts, and policy reform.ResultsOf the 3,684 survey respondents, about a third (33.0%, 1,216/3,684) of screened households reported diagnostic problems and mistakes in the past four years involving either themselves (18.9%, 697/3,684) or someone close to them (14.1%, 519/3,684). In the aftermath of a diagnostic mishap, over a third reported that someone in the healthcare setting where the mistake occurred acknowledged the mistake (35.9%, 432/1,204). In qualitative findings, reports that the health system “did nothing” surfacing as the most common response. Patient co-authors confirmed the results resonated with their experiences and emphasized the need for health systems to take accountability when a mishap occurs and to take follow-up actions to prevent future mishaps.DiscussionPatients and care partners not only want and deserve acknowledgement of diagnostic problems or mistakes in their own care, they also want assurance that steps are being taken to prevent similar events from happening to others. Across micro-, meso-, and macro-levels of action, working with patients to understand and act on contributors to diagnostic breakdowns is aligned with high-reliability organizing principles.